2017
DOI: 10.1371/journal.pone.0178202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel glucose capped gold nanoparticle as a better theranostic candidate

Abstract: Gold nanoparticles are predominantly used in diagnostics, therapeutics and biomedical applications. The present study has been designed to synthesize differently capped gold nanoparticles (AuNps) by a simple, one-step, room temperature procedure and to evaluate the potential of these AuNps for biomedical applications. The AuNps are capped with glucose, 2-deoxy-D-glucose (2DG) and citrate using different reducing agents. This is the first report of synthesis of 2DG-AuNp by the simple room temperature method. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…The use of nanotechnology to produce metallic nanostructures has gained interest, especially in medicine [ 17 , 18 , 19 ]. The fascinating and insightful use of optical, chemical and catalytic properties of noble metal NPs depends on the metal source, nanoparticle sizes and shapes and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanotechnology to produce metallic nanostructures has gained interest, especially in medicine [ 17 , 18 , 19 ]. The fascinating and insightful use of optical, chemical and catalytic properties of noble metal NPs depends on the metal source, nanoparticle sizes and shapes and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that glucose-stabilized gold nanoparticles exhibit a strong surface plasmonic peak at 540 nm, for nanoparticles with diameter of 19 nm. 38 In the case of the Fe 3 O 4 @AuNPs covered with layers of Au in two steps, the surface plasmon resonance peak is shifted towards higher wavelengths, indicating that the thickness of the Au shell has increased. Moreover, the surface plasmon resonance peak is both sharper and more intense in the case of Fe 3 O 4 @AuNPs covered with Au in two steps, suggesting that the Au shell became more uniform in the latter case.…”
Section: Synthesis and Characterization Of Fe 3 O 4 @Aunpsmentioning
confidence: 97%
“…To overcome non-specic aggregation and low specicity, we explored sucrose as a capping agent. 16,20,21 Sucrose-capped AuNPs were synthesized using the two different methods (termed Type 1 and Type 2, ESI Table 1 ‡). The two methodologies yielded particles with sizes in the range of 49.23 nm (AE0.44 nm) and 90.12 nm (AE14.32) for Type 1 and Type 2 particles, respectively (ESI Fig.…”
Section: Capping Agents Inuence Particle Stability and Sensitivity Omentioning
confidence: 99%